Comparative decay of sewage-associated marker genes in beach water and sediment in a subtropical region. (1st February 2019) - Ahmed, Warish; Zhang, Qian; Kozak, Sonya; Beale, David; Gyawali, Pradip; Sadowsky, Michael J.; Simpson, Stuart
Abstract: There is a growing move towards using the quantitative polymerase chain (qPCR)-based sewage-associated marker genes to assess surface water quality. However, a lack of understanding about the persistence of many sewage-associated markers creates uncertainty for those tasked with investigating microbial water quality. In this study, we investigated the decay of two qPCR FIB [ E. coli (EC), and Enterococcus spp. (ENT) 23S rRNA genes] and four sewage-associated microbial source tracking (MST) marker genes [human Bacteroides HF183 16S rRNA, adenovirus (HAdV), and polyomavirus (HPyV), and crAssphage, a recently described bacteriophage in feces], in outdoor mesocosms containing fresh and marine waters and their corresponding sediments. Decay rates of EC 23S rRNA, ENT 23S rRNA, and HF183 16S rRNA were significantly ( p < 0.05) faster than the HAdV, HPyV and crAssphage markers in water samples from all mesocosms. In general, decay rates of bacterial targets were similar in the water columns of the studied mesocosms. Similarly, decay rates of viral targets were also alike in mesocosm water columns in relation to each other. The decay rates of FIB and sewage-associated markers were significantly faster in water samples compared to sediments in all three mesocosms. In the event of resuspension, FIB and marker genes from sediments can potentially recontaminate overlying waters. Thus, care should be taken when interpreting the occurrence of FIB and sewage-associated MST markers in water, which may have originated from sediments. The differential decay of these targets may also influence health outcomes and need to be considered in risk assessment models. Graphical abstract: Image 1 Highlights: Decay rates of bacterial gene markers were significantly faster than the viruses. Markers decay rates were significantly faster in water samples compared to sediments. Decay rates of marker genes were similar for both fresh and marine waters. Markers decay positively correlated with water temperature, TOC, and turbidity.